A solid-state Frisch gate device based on perovskite material and a preparation method thereof
By embedding the gate grid in perovskite semiconductor materials and adjusting the weight potential field distribution, the problems of uneven weight potential field and incomplete signal shielding in virtual Frisch gate devices are solved, and higher temporal and spatial resolutions are achieved, and energy spectrum information can be obtained more accurately.
Patent Information
- Application Number
- CN202411415000.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing virtual Frisch gate devices have problems such as uneven weight potential field and incomplete signal shielding, which leads to poor transmission performance of carriers, low time and spatial resolution, and it is difficult to achieve accurate energy spectrum information acquisition.
A solid-state Frisch gate device based on perovskite materials is used to adjust the shape, thickness and thickness of the gate grid in the crystal to achieve a more uniform and controllable weight potential field distribution.
A more uniform weight potential field distribution is achieved, the charge shielding effect is improved, the device's time and spatial resolution is enhanced, and the energy and position information of the beams can be reflected more accurately.
Smart Images

Figure CN118943233B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor detection, and in particular relates to a solid-state Frisch gate device based on perovskite material and a preparation method thereof. Background Art
[0002] The gas ionization chamber is one of the earliest detectors used in nuclear science applications. Its working principle is that under radiation conditions, gas molecules are ionized or excited to produce a large number of electron-ion pairs, and the relevant radiation information is obtained by detecting the generated electrons and positive ions. It has the characteristics of simple structure and easy production. In the gas ionization chamber, the effective mass and volume of electrons are much smaller than those of positive ions, and they have a larger mean free path. Therefore, most gas ionization chambers use electrons as the main carriers. However, electrons will collide and be captured to form negative ions during movement, resulting in a variety of charge effects in the gas ionization chamber, such as diffusion, adsorption, recombination, and drift, which leads to charge loss during the transmission process of carriers.
[0003] In a gas ionization chamber, the effective mass of electrons is small, and due to various charge effects, their drift speed is about 3 orders of magnitude higher than that of positive ions. Therefore, when electrons drift to the anode, positive ions will still induce a slower induction signal, which is not conducive to the rapid measurement of pulse signals. This phenomenon is particularly significant when detecting particles with ionization trajectory directions ( Figure 1 a and b). To address this problem, Frisch (Frisch O. British atomic energy report br-49 [J]. Atomic Energy Research Establishment: Harwell, UK, 1944.) proposed a Frisch gate device structure ( Figure 1 c), the device uses a metal grid to establish an electrostatic shield in the gas medium, which can effectively shield the induction signal of positive ions during the drift process, thereby realizing the signal collection of a single carrier (electron). Experiments have shown that by shielding the charge of positive ions, the device structure can speed up the device's time response ( Figure 1 d). Specifically, Figure 1 As shown in a, the weighted potential field of the planar device is linearly distributed. The huge difference in the mobility of the two carriers will seriously affect the charge collection time at different positions of the ray, resulting in differences in the order of the termination nodes of the induced charge, thus affecting the final amplitude ( Figure 1 b). In comparison, Figure 1Figure c shows the weight potential distribution of a Frisch gate detector with an electrostatic shielding grid, where the gate can effectively shield the induced charge of slow carriers, so that the amplitude of the device depends only on fast carriers, so that the rise time and amplitude of the carriers induced by rays at different action positions are basically the same ( Figure 1 d), so that the device can more accurately reflect the energy of the rays.
[0004] Similar to gas ionization chambers, semiconductor detectors (i.e., solid ionization chambers) use solid semiconductor materials as the medium. The inconsistent electrostatic interactions between atoms in the material lead to obvious differences in the transmission performance of electron and hole carriers. Due to the limitations of material synthesis and processing technology, it is not possible to build a shielding grid into the semiconductor, so it is still impossible to realize a solid-state Frisch grid detector similar to a gas ionization chamber detector. In 1998, McGregor (Mcgregor D, He Z, Seifert H, et al. CdZnTe semiconductor parallel strip Frisch grid radiation detectors [J]. IEEE Transactions on Nuclear Science, 1998, 45 (3): 443-449.) borrowed from the gas ionization chamber and used cadmium zinc telluride (CdZnTe) crystals to realize a virtual Frisch grid structure. For example Figure 2As shown in a, the main body of the virtual Frisch gate device is a planar device structure consisting of a cathode, a semiconductor material, and an anode. Afterwards, an insulating layer is wrapped around the outside of the crystal to shield the charge between the collector and the Frisch gate. Finally, a Frisch gate (metal electrode) is wrapped on the side close to the collector to obtain the charge shielding effect on the collector side. Further research shows that adding an insulating layer between the crystal and the gate can effectively reduce the gate's absorption of carriers, and the thickness of the insulating layer is relatively thin, which is equivalent to a capacitor. The gate can still sense signals during the carrier drift process (Montémont G, Argues M, Verger L, et al. A capacitive Frisch grid structure for CdZnTe detectors[C].2000 IEEENuclear Science Symposium. Conference Record (Cat. No. 00CH37149),2000: 4 / 9-412.). Since then, the virtual Frisch grid structure has also been applied to semiconductor crystals such as TlBr (Hitomi K, Tada T, Onodera T, et al. TlBr capacitive Frisch grid detectors [J]. IEEE Transactions on Nuclear Science, 2012, 60 (2): 1156-1161.) and CdZnTeSe (Roy UN, Camarda GS, Cui Y, et al. Evaluation of CdZnTeSe as a high-quality gamma-ray spectroscopic material with better compositional homogeneity and reduced defects [J]. Scientific reports, 2019, 9 (1): 7303.) to improve the energy spectrum performance of the detector. However, existing unipolar devices (hemispherical type, pixel type, etc.), including virtual Frisch grids, still have widespread problems such as non-uniform weight potential field and incomplete signal shielding, which discretizes the distribution characteristics of the collected signal. Therefore, developing and optimizing the weighted potential field distribution of devices based on semiconductor materials has extremely important scientific significance and practical value for obtaining accurate energy spectrum information and reducing signal rise time.
[0005] The new halide perovskite semiconductor, with its excellent carrier transport performance and defect tolerance, is expected to become a new generation of room-temperature semiconductor nuclear radiation detection materials. The unique advantage of halide perovskites is that they can be prepared by low-temperature solution method, the device structure is more flexible, and the manufacturing cost of the device can be significantly reduced. Based on the high defect tolerance of halide perovskites, by introducing filaments or gates during the crystal growth process, the shielding effect can be more effectively introduced, the weighted potential field can be optimized, and finally a true solid-state Frisch gate device structure ( Figure 3 ). To date, conventional room temperature semiconductor detectors use virtual Frisch gate structures to optimize the weighted potential field. The device structure is exemplified by CdZnTe, such as Figure 2 As shown in a in the figure, the cathode, CdZnTe and anode are simple planar (sandwich) device structures, the anode is an electron collector, and then an insulating layer is wrapped around the outside of the CdZnTe crystal, and a metal layer is wrapped around the side close to the anode as a gate.
[0006] In addition, for semiconductors, researchers have also developed other unipolar detection devices, such as hemispherical, pixel-type and coplanar gates. The weighted potential field distribution of these devices at the collecting electrode is similar to that of the virtual Frisch gate device.
[0007] To date, no true solid-state Frisch gate device has been realized in traditional compound semiconductor detectors (such as CdTe and CdZnTe). Summary of the invention
[0008] The disadvantages of the prior art are as follows:
[0009] 1. If Figure 2 As shown in a, the existing virtual Frisch gate device structure is mainly based on planar devices. From the perspective of weight potential field optimization, the only adjustable parameters are the thickness and height of the insulating layer, the gate height, etc. Since the virtual Frisch gate only acts on the outer layer of the device, the adjustment of these parameters has limited effect on the optimization of the weight potential field. Figure 2 As shown in Figure b, the weight potential of the virtual Frisch gate device is not uniform in the X and Y axis directions, that is, the weight potential distribution at the center is closer to being dispersed toward the cathode, and the weight potential distribution at the edge is closer to being concentrated toward the anode. This inhomogeneity of the weight potential field leads to inconsistent shielding effects at different positions, which leads to complex pulse shape distribution, further limiting its application range. In addition, the pulse waveform contains information such as the depth of action of the ray and the drift time of the carrier. This inhomogeneous weight potential field will seriously weaken the time and space resolution of the device.
[0010] 2. In order to ensure the shielding effect, the virtual Frisch gate device has relatively strict requirements on the crystal size and gate height. Generally speaking, the crystal of the virtual Frisch gate device needs to be equal in length and width, the height is twice the length and width, and the gate height must be greater than or equal to the length and width to achieve a good shielding effect. It can be seen that the virtual Frisch gate device is suitable for rectangular crystals and limits the electrode direction, making it difficult to use large-area, low-height crystals to achieve weight potential optimization.
[0011] 3. In hemispherical devices, due to the uneven distribution of the electric field, there are large differences in the pulse shapes, and it is currently impossible to further electronically correct the signal.
[0012] 4. In pixel-type devices, the unipolar signal sensitivity is mainly obtained by the small pixel effect, which requires at least N 2 The number of electronic readout channels (N is the number of pixels) greatly increases the design and readout complexity of the electronic system. Due to the expansion of the weighted potential field, the induced charge regions between different pixels overlap, resulting in charge sharing events, which further increases the difficulty of signal processing.
[0013] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0014] The present invention provides a solid-state Frisch gate device based on perovskite material, comprising a crystal and a grid embedded in the crystal; an anode and a cathode are respectively arranged at two ends of the crystal, and the grid, the anode and the cathode are arranged in parallel;
[0015] The grid is composed of several layers of gate metal sheets and an insulating layer wrapping the metal sheets, and the gate metal sheets are arranged between the cathode and the anode of the crystal; the crystal is selected from three-dimensional organic-inorganic hybrid perovskite, all-inorganic perovskite, two-dimensional perovskite, zero-dimensional perovskite or double perovskite.
[0016] Preferably, the chemical formula of the three-dimensional organic-inorganic hybrid perovskite and the all-inorganic perovskite is APbX3, wherein A is selected from methylamine cation (MA + ), ethylamine cation (FA + ) or Cs + , X is selected from F - , Cl - Br - or I - The chemical formula of the two-dimensional perovskite is A3B2X9, wherein A is selected from ammonium ions (NH4 + ), methylamine cation (MA + ), ethylamine cation (FA + )、Cs + or Rb + , B is selected from Sb 3+ Or Bi3+ , X is selected from Br - or I - ; The chemical formula of the zero-dimensional perovskite is Cs3Bi2I9, Cs2TeI6 or Cs2TeBr6; the chemical formula of the double perovskite is Cs2AgBiBr6.
[0017] Preferably, the material of the gate metal sheet is selected from gold, copper, tungsten or stainless steel.
[0018] Preferably, the shape of the grid is selected from one or more of a wire type, a strip type, a mesh type, a hole type and a honeycomb type.
[0019] The grid structure of the present invention includes but is not limited to different regular or irregular metal styles such as wire type, strip type, mesh type, hole type, honeycomb type, and combinations of the above different styles (such as Figure 3 of ad).
[0020] Preferably, the thickness of the grid is 1 nm-50 mm.
[0021] Preferably, the thickness of the insulating layer is 0-500 µm. Depending on actual needs, there may be a situation where an insulating layer is not required.
[0022] Preferably, the material of the insulating layer is selected from inorganic insulating materials or organic insulating materials; the inorganic insulating material is selected from AlN, Al2O3 or SiO2, and the organic insulating material is selected from C-type parylene, N-type parylene, polytetrafluoroethylene, paraffin or acrylic.
[0023] Preferably, the materials of the anode and cathode are both selected from platinum, gold, silver, gallium, indium, lead or bismuth.
[0024] The present invention also provides a method for preparing the above-mentioned solid-state Frisch gate device based on perovskite material, wherein the preparation method example is selected from one or more of solution direct crystal growth, mechanical processing and crystal bonding;
[0025] The solution method for direct crystal growth comprises the following steps:
[0026] S11: After placing the grid on top of the bottom crystal, the crystal grows in the precursor solution;
[0027] S12: preparing an anode and a cathode respectively on the top and bottom of the crystal grown in the step S11 to obtain the solid-state Frisch gate device based on the perovskite material;
[0028] The mechanical processing method comprises the following steps:
[0029] S21: cutting the bottom crystal to form cutting grooves and then embedding the grid;
[0030] S22: placing the crystal embedded with the grid in step S21 in a precursor solution for growth;
[0031] S23: preparing an anode and a cathode respectively on the top and bottom of the crystal grown in step S22 to obtain the solid-state Frisch gate device based on the perovskite material;
[0032] The crystal bonding method comprises the following steps:
[0033] S31: coating the surface of the bottom crystal A with a precursor solution and then covering the grid;
[0034] S32: Covering the stacked crystal B on the top of the bottom crystal A covered with the grid in step S31;
[0035] S33: Under the action of the precursor solution, a crystal C is grown in the gap between the bottom crystal A and the stacked crystal B in step S32 to obtain a crystal with an embedded grid; the composition of the crystal C and the stacked crystal B is the same as that of the bottom crystal A;
[0036] S34: preparing an anode and a cathode at the top and bottom of the crystal with the embedded grid, respectively, to obtain the solid-state Frisch gate device based on the perovskite material.
[0037] Preferably, in the precursor solution, the solvent is an organic solvent, and the solute is several metal salts; the cations and anions in the metal salts are selected from the chemical elements in the crystal.
[0038] Furthermore, according to different properties of the perovskite crystals, the organic solvent is selected from a solution that can dissolve the perovskite material, including but not limited to one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) and γ-butyrolactone (GBL).
[0039] Preferably, the organic solvent is dimethyl sulfoxide (DMSO).
[0040] Specifically, the Frisch gate device structure proposed in the present invention can have multiple preparation schemes, including but not limited to the following three, which are demonstrated below using cesium lead bromine (CsPbBr3) perovskite crystal as an example:
[0041] Example 1 of the complete technical process of the present invention, such as Figure 4 As shown, the specific steps are as follows:
[0042] 1. Seed crystal growth. Figure 4 As shown in a, a DMSO solution with a molar ratio of CsBr to PbBr2 of 1:2 is used as a precursor solution to grow CsPbBr3 seed crystals at a concentration of 0.9 mol / L, and suitable seed crystals are selected for subsequent crystal growth;
[0043] 2. Over-gate growth. Figure 4 As shown in b, a grid with an insulating layer is placed above the CsPbBr3 seed crystal, and the seed crystal continues to grow in the precursor solution. The seed crystal stops growing after it grows to completely cover the grid and has a certain size, as shown in FIG. Figure 4 As shown in c;
[0044] 3. Device preparation. Take out the CsPbBr3 crystal with the grid inside from the solution, and prepare gold and gallium-indium alloy as cathode and anode on the upper and lower surfaces of the crystal respectively ( Figure 4 d, e), thus obtaining a solid-state Frisch gate detector based on CsPbBr3 crystal.
[0045] 4. Device testing. Figure 4 As shown in f, a negative high voltage is applied to the cathode (gold electrode) of the solid-state Frisch gate detector, a positive high voltage is applied to the anode (gallium-indium alloy electrode), the gate is grounded or no voltage is applied, and the signal on the electrode is connected to the readout system, so as to obtain the pulse waveform information or energy spectrum of the device.
[0046] Example 2 of the gate preparation technology process of the present invention, such as Figure 5 As shown, the specific steps are as follows:
[0047] 1. Crystal preparation. Select CsPbBr3 single crystals with suitable length, height and width for preparing solid-state Frisch gate detectors, such as Figure 5 As shown in a;
[0048] 2. Crystal processing. Figure 5 As shown in b, a diamond wire cutting machine, laser cutting and other processing techniques are used to process one side of the CsPbBr3 crystal so that it matches the grid;
[0049] 3. Insert the grid. Place the grid of a certain size and shape into the cutting groove, close to the crystal, such as Figure 5 As shown in c;
[0050] 4. Crystal regrowth. Place the CsPbBr3 crystal with embedded grid into the DMSO precursor solution, so that the CsPbBr3 crystal grows and fills the processed cutting groove, so that the grid is embedded in the crystal. Figure 5 As shown in d;
[0051] 5. Subsequent device preparation and test reference Figure 4 df.
[0052] Example 3 of the gate preparation technology process of the present invention, such as Figure 6 As shown, the specific steps are as follows:
[0053] 1. Crystal preparation. Figure 6 As shown in a, CsPbBr3 crystals A and B with suitable shapes and sizes are screened for preparing solid-state Frisch gate detectors;
[0054] 2. Add solution dropwise. Figure 6 As shown in b, a DMSO precursor solution is dripped onto the upper surface of CsPbBr3 crystal A for subsequent growth;
[0055] 3. Cover the grid and crystal. Figure 6 As shown in c, a grid of a certain size and shape and a CsPbBr3 crystal B are sequentially covered on the CsPbBr3 crystal A and the precursor solution;
[0056] 4. Growth of crystal gaps. Figure 6 As shown in d, under the action of the precursor solution, CsPbBr3 grows in the gap between crystals A and B, and the two crystals A and B are connected, and finally a CsPbBr3 crystal with an embedded grid is obtained;
[0057] 5. Subsequent device preparation and test reference Figure 4 df.
[0058] In view of the inherent defects of the existing virtual Frisch gate structure, the present invention proposes a solid-state Frisch gate device based on perovskite semiconductor materials. The specific preparation method includes direct growth using a solution method and mechanical processing. Figure 3 ad are four different grid types designed (note: not limited to these four grid types, can also include honeycomb type, irregular polygon and other shapes), the corresponding weight potential field distribution diagram in the Y and Z directions at X = 1.5 mm is shown in Figure 3 As shown in eh. It can be clearly seen from the figure that the weight potential field distribution of the device is greatly restricted at the grid position, indicating that the gate can play a good charge shielding effect. In addition, by comparing the weight potential distributions of different grids, it can be found that the solid-state Frisch gate structure used in the present invention can achieve a more uniform and near-ideal weight potential field distribution by adjusting the grid parameters. In addition, by further analyzing the signals of the anode, cathode, and gate of independent events, more accurate pulse rise time information and ray action position information can be obtained.
[0059] The solid-state Frisch gate structure of the present invention is applicable to perovskite crystals of all sizes and can be used as one of the best optimization solutions for the weighted potential field of semiconductor detectors. Moreover, compared with pixel-type devices, the readout system of solid-state Frisch gate devices is very simple, requiring only a single-channel readout, and in principle, the pulse waveform does not require complex electronic correction.
[0060] The technical solution of the present invention has the following advantages over the prior art:
[0061] The present invention utilizes the characteristics of halide perovskite that it can be prepared by low-temperature solution method and has high defect tolerance, and directly grows a crystal with a Frisch gate structure, thereby realizing a true solid-state Frisch gate device structure and solving the following problems:
[0062] 1. Compared with the existing unipolar devices, in the present invention, since the grid structure is directly embedded in the crystal, the distribution of the weighted potential field and its shielding effect can be effectively controlled, and the time resolution of the device can be improved. Figure 3 shown.
[0063] 2. In the present invention, by adjusting the grid parameters, such as the grid height (the distance between the grid and the collector), the grid thickness, the grid aperture, and the thickness of the insulating layer, different weighted potential field distributions can be obtained, and the distribution is more uniform and controllable. Among them, the thinner the grid, the smaller its impact on crystal growth, which is conducive to obtaining large-sized crystals and increasing the detection volume, but the shielding effect increases with the increase of the grid thickness; the smaller the distance between the grid and the collector, the more concentrated the weight potential will be on the collector; the denser the grid (smaller the aperture), the more uniform the distribution of its weight potential in the horizontal plane. Compared with virtual Frisch gate devices, the applicable crystal size is wider.
[0064] 3. The grid structure embedded in the crystal improves the uniformity of the weighted potential field distribution, making the signal inflection point at the gate clear. The action position of the ray between the gate and the non-collecting electrode can be determined according to the drift time, so the present invention has a higher spatial resolution than the virtual Frisch grid.
[0065] 4. Compared with pixel-type devices, the structure of the present invention is improved based on planar devices, and the readout electrodes only have three cathodes, anodes, and gates, which greatly simplifies the readout difficulty of the back-end electronics. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 (a) Schematic diagram of planar device and internal weighted potential field distribution; (b) Schematic diagram of rise time and amplitude at different ray action positions in planar device; (c) Schematic diagram of Frisch gate device and internal weighted potential field distribution; (d) Schematic diagram of rise time and amplitude at different ray action positions in Frisch gate device.
[0067] Figure 2 (a) Schematic diagram of the virtual Frisch gate device structure of CdZnTe crystal; (b) the section weighted potential field distribution of the CdZnTe virtual Frisch gate detector with a crystal size of 3.1×3.1×4.0 mm and a gate height of 1 mm at X = 1.5 mm.
[0068] Figure 3Schematic diagrams of the Frisch grating structures of mesh type (a), hole type (b), strip hole type (c), and wire type (d). (e - h) are the corresponding cross-sectional weighted potential field distribution diagrams of the solid-state Frisch grating detector at X = 1.5 mm.
[0069] Figure 4 Schematic diagram of the preparation of solid-state Frisch gate devices based on CsPbBr3 crystals: (a) seed crystal growth; (b) adding a grid; (c) over-gate growth; (d) cathode preparation; (e) anode preparation; (f) signal collection.
[0070] Figure 5 Schematic diagram of the preparation of solid-state Frisch gate devices based on CsPbBr3 crystals Figure 2 :(a) Crystal preparation; (b) Crystal processing; (c) Grid embedding; (d) Crystal regrowth.
[0071] Figure 6 Schematic diagram of the preparation of solid-state Frisch gate devices based on CsPbBr3 crystals Figure 3 :(a) Crystal preparation; (b) Adding CsPbBr3 growth precursor solution; (c) Covering grid and crystal; (d) Crystal regrowth.
[0072] Figure 7 (a) The weight potential distribution diagram of the grid-type solid-state Frisch gate device with different gate heights. The weight potential increases sharply near the gate; (b) Comparison of cathode, anode, and gate pulse waveforms of the solid-state Frisch gate device. The inset is the CsPbBr3 solid-state Frisch gate crystal grown in Example 1; (c) The CsPbBr3 solid-state Frisch gate detector 137 Scatter plot of Cs pulse height and drift time distribution; (d) after height correction 137 Cs energy spectrum. DETAILED DESCRIPTION
[0073] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention. Example 1
[0074] CsBr and PbBr2 with a molar ratio of 1:2 were dissolved in DMSO solution with a concentration of about 0.9 mol / L, and heated to 60 ℃ and stirred to completely dissolve. A clear saturated precursor solution was obtained by filtering with 0.22 μm PTFE. Subsequently, CsPbBr3 crystals were grown by inversion crystallization. When the crystals grew to about 1 mm, a copper mesh grid (grid thickness 0.05 mm) coated with a 10 μm thick Al2O3 insulating layer was placed above the crystals. The crystals continued to grow in the precursor solution and passed through the grid. When the grid was perfectly embedded in the crystals and the crystals grew to a certain size, they were taken out. The cathode was made of gold glue on the lower surface of the crystal, and the anode was made of gallium-indium alloy on the upper surface, to obtain a mesh-type solid-state Frisch gate device based on CsPbBr3 crystals. The cathode, anode, and gate signals were respectively led out through wires, and negative high voltage was applied to the cathode, positive high voltage was applied to the anode, and no voltage was applied to the gate. The signal response and energy spectrum of the device were tested. Example 2
[0075] CsBr and PbBr2 with a molar ratio of 1:2 were dissolved in DMSO solution with a concentration of about 0.9 mol / L, and heated to 60℃ and stirred to completely dissolve. A clear saturated precursor solution was obtained by filtering with 0.22 μm PTFE. Subsequently, CsPbBr3 crystals were grown by inversion crystallization. When the crystals grew to about 1 mm, a stainless steel wire-type grid (wire diameter 0.01 mm) coated with a 50 μm thick SiO2 insulating layer was placed above the crystals. The crystals continued to grow in the precursor solution and passed through the grid. When the grid was perfectly embedded in the crystals and the crystals grew to a certain size, they were taken out. A cathode was made of gold glue on the lower surface of the crystals, and bismuth was evaporated on the upper surface as an anode to obtain a wire-type solid-state Frisch gate device based on CsPbBr3 crystals. The cathode, anode, and gate signals were respectively led out through wires, and negative high voltage was applied to the cathode, positive high voltage was applied to the anode, and no voltage was applied to the gate. The signal response and energy spectrum of the device were tested. Example 3
[0076] A γ-butyrolactone solution with a molar ratio of MAI to PbI2 of 1:1 and a concentration of 1.5 mol / L was used as the precursor solution, and MAPbI3 crystals were grown by the inversion crystallization method. When the crystal grew to about 1 mm, it was used as a seed crystal. A gold hole-shaped grid with parylene C as an insulating layer (thickness 500 μm) was placed on the seed crystal, and the crystal continued to grow in the precursor solution and pass through the grid. When the grid was embedded in the crystal and the crystal grew to a certain size, it was taken out, platinum was sputtered on the lower surface of the crystal as a cathode, and metal indium was evaporated on the upper surface as an anode to obtain a hole-shaped solid-state Frisch gate device based on MAPbI3 crystal. The cathode, anode, and gate signals were respectively led out through wires, and negative high voltage was applied to the cathode, positive high voltage was applied to the anode, and no voltage was applied to the gate. The signal response and energy spectrum of the device were tested. Example 4
[0077] CsPbBr3 single crystals were grown using the Bridgman method with a molar ratio of 1:1 between CsBr and PbBr2. A 2×2×4 mm crystal was obtained by grinding and polishing. A wire cutter was used to process one side of the crystal so that the cutting groove matched the grid. A grid with a thickness of 0.1 mm, a wire diameter of 0.01 mm, and a wire pitch of 1 mm was embedded in the cutting groove. The crystal and the grid were placed in a saturated CsPbBr3 solution and grown again, so that the crystal filled the pores and obtained a CsPbBr3 crystal with a grid. The cathode was made of gold glue on the lower surface of the crystal, and the anode was made of gallium-indium alloy on the upper surface, and a mesh-type solid-state Frisch gate device based on CsPbBr3 crystal was obtained. The cathode, anode, and gate signals were respectively led out through wires, and negative high voltage was applied to the cathode, positive high voltage was applied to the anode, and no voltage was applied to the gate. The signal response and energy spectrum of the device were tested. Example 5
[0078] CsPbBr3 single crystals were grown using the Bridgman method with a molar ratio of 1:1 between CsBr and PbBr2. Crystals A and B of 2×2×2 mm were obtained by grinding and polishing. A saturated solution of CsPbBr3 was dripped onto crystal A, covering the grid and crystal B. The solvent was evaporated using the evaporation method to allow CsPbBr3 crystals to grow between the pores, and crystal A, grid, and crystal B were connected to obtain a CsPbBr3 crystal with a grid. A cathode was made of gold glue on the lower surface of the crystal, and an anode was made of gallium-indium alloy on the upper surface to obtain a mesh-type solid-state Frisch gate device based on CsPbBr3 crystals. The cathode, anode, and gate signals were respectively led out through wires, and negative high voltage was applied to the cathode, positive high voltage was applied to the anode, and no voltage was applied to the gate. The signal response and energy spectrum of the device were obtained by testing.
[0079] Effect evaluation 1
[0080] based on Figure 3The weight potential field distribution of the solid-state Frisch gate device in e can be obtained by adjusting the gate height at X = 1.5 mm and Y = 1.5 mm along the Z axis, as shown in Figure 7 As shown in a. As can be seen from the figure, the gate height significantly affects the weighted potential field distribution of the device, and its shielding effect decreases with the decrease of the gate height. When the gate height of the device is 1 mm, the weighted potential field distribution on the anode side can be limited to a lower level, and the induced charge generated by the target carrier in this area is low. Figure 7 Figure b shows the pulse waveforms of the anode, gate, and cathode of a solid-state Frisch gate detector based on CsPbBr3 crystals, and the inset is the CsPbBr3 solid-state Frisch gate grown in Example 1. It can be seen from the figure that in the initial stage, the anode responds earlier than the cathode, indicating that the rays act on the area between the anode and the gate at this time; when the generated carriers begin to drift under the action of the electric field, the anode and the gate generate induced signals in opposite directions (that is, the anode signal is positive and the gate signal is negative); when the carriers pass through the gate and begin to move away from the gate, the anode signal is shielded by the gate, the induced signal decreases, the anode height reaches the maximum and begins to decay before the cathode and the gate, and the hole carriers induced by the cathode pass through a larger weight potential field difference, so the cathode signal begins to increase rapidly, and the signal direction is negative, and the gate begins to generate a positive signal, which appears as a bipolar signal. According to the prepared solid-state Frisch gate device, the following is obtained Figure 7 The c shows 662 keV 137 The scatter plot of cathode height and drift time of Cs γ-ray response. The top of the figure shows two scatter plots with the same slope, corresponding to 137 The 662 keV full energy peak of Cs and the escape peak of Pb. In addition, the cathode height can decay by about 10% with the increase of drift time, indicating that the carrier mobility of the CsPbBr3 crystal grown by the solution method is low, resulting in attenuation during the drift process, and the farther away from the gate, the more serious the attenuation. It also verifies that the prepared solid-state Frisch gate device can obtain the radiation energy and position information within the entire deposition range. Then, the pulse height with different drift times is energy corrected, such as Figure 7 As shown in d.
[0081] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A solid-state Frisch gate device based on perovskite material, characterized in that: It comprises a crystal and a grid embedded in the crystal; an anode and a cathode are respectively arranged at two ends of the crystal, and the grid, the anode and the cathode are arranged in parallel; The grid is composed of several layers of gate metal sheets and an insulating layer wrapping the gate metal sheets, wherein the gate metal sheets are arranged between the cathode and the anode of the crystal; the crystal is selected from three-dimensional organic-inorganic hybrid perovskite, all-inorganic perovskite, two-dimensional perovskite, zero-dimensional perovskite or double perovskite; the chemical formula of the three-dimensional organic-inorganic hybrid perovskite and all-inorganic perovskite is APbX3, wherein A is selected from methylamine cation, ethylamine cation or Cs + , X is selected from F - , Cl - Br - or I - The chemical formula of the two-dimensional perovskite is A3B2X9, wherein A is selected from ammonium ions, methylamine cations, ethylamine cations, Cs + or Rb + , B is selected from Sb 3+ Or Bi 3+ , X is selected from Br - or I - ; The chemical formula of the zero-dimensional perovskite is Cs3Bi2I9, Cs2TeI6 or Cs2TeBr6; the chemical formula of the double perovskite is Cs2AgBiBr6.
2. The solid-state Frisch gate device based on perovskite material as claimed in claim 1, characterized in that: The material of the gate metal sheet is selected from gold, copper, tungsten or stainless steel.
3. The solid-state Frisch gate device based on perovskite material as claimed in claim 1, characterized in that: The shape of the grid is selected from one or more of a wire type, a strip type, a mesh type, a hole type and a honeycomb type.
4. The solid-state Frisch gate device based on perovskite material according to claim 1, characterized in that: The thickness of the grid is 1 nm-50 mm.
5. The solid-state Frisch gate device based on perovskite material as claimed in claim 1, characterized in that: The thickness of the insulating layer is 0-500 μm.
6. The solid-state Frisch gate device based on perovskite material according to claim 1, characterized in that: The material of the insulating layer is selected from inorganic insulating materials or organic insulating materials; the inorganic insulating material is selected from AlN, Al2O3 or SiO2, and the organic insulating material is selected from C-type parylene, N-type parylene, polytetrafluoroethylene, paraffin or acrylic.
7. The solid-state Frisch gate device based on perovskite material according to claim 1, characterized in that: The materials of the anode and cathode are selected from platinum, gold, silver, gallium, indium, lead or bismuth.
8. A method for preparing a solid-state Frisch gate device based on a perovskite material according to any one of claims 1 to 7, characterized in that: The preparation method is selected from one of solution method direct crystal growth, mechanical processing and crystal bonding; The solution method for direct crystal growth comprises the following steps: S11: After placing the grid on top of the bottom crystal, the crystal is placed in the precursor solution for growth; S12: preparing an anode and a cathode respectively on the top and bottom of the crystal grown in the step S11 to obtain the solid-state Frisch gate device based on the perovskite material; The mechanical processing method comprises the following steps: S21: cutting the bottom crystal to form cutting grooves and then embedding the grid; S22: placing the crystal embedded with the grid in step S21 in a precursor solution for growth; S23: preparing an anode and a cathode respectively on the top and bottom of the crystal grown in step S22 to obtain the solid-state Frisch gate device based on the perovskite material; The crystal bonding method comprises the following steps: S31: coating the surface of the bottom crystal A with a precursor solution and then covering the grid; S32: Covering the stacked crystal B on the top of the bottom crystal A covered with the grid in step S31; S33: Under the action of the precursor solution, a crystal C is grown in the gap between the bottom crystal A and the stacked crystal B in step S32 to obtain a crystal with an embedded grid; the composition of the crystal C and the stacked crystal B is the same as that of the bottom crystal A; S34: preparing an anode and a cathode at the top and bottom of the crystal with the embedded grid, respectively, to obtain the solid-state Frisch gate device based on the perovskite material.
9. The preparation method according to claim 8, characterized in that: In the precursor solution, the solvent is an organic solvent, and the solute is several kinds of metal salts; the cations and anions in the metal salts are selected from the chemical elements in the crystal.
Citation Information
Patent Citations
Coplanar gate anode tellurium-zinc-cadmium detector with capacitor gate and method for making same
CN101038942A
Preparation technology of CdZnTe detector of capacitance Frisch bars
CN103094405A